SLC35B4 Stabilizes c-MYC Protein by O-GlcNAcylation in HCC - Jiang, Tao; Yang, Jinghong; Yang, Huohong; Chen, Wancheng; Ji, Kaiyuan; Xu, Yang; Yu, Lili (Frontiers in Pharmacology, 2022)
UDP-GlcNAc is a sugar substrate necessary for the O-GlcNAcylation of proteins. SLC35B4 is one of the nucleotide sugar transporters that transport UDP-GlcNAc and UDP-Xylose into endoplasmic reticulum (ER) and Golgi apparatus for glycosylation. The roles of SLC35B4 in HCC tumorigenesis remains unknown. We find that the expression levels of SLC35B4 are higher in hepatocellular carcinomas (HCC) tissues than adjacent non-tumor tissues. SLC35B4 is important for the proliferation and tumorigenesis of HCC cells. Mechanistically, SLC35B4 is important for the O-GlcNAc modification of c-Myc and thus the stabilization of c-Myc, which is required for HCC tumorigenesis. Therefore, SLC35B4 is a promising therapeutic target for treating HCC.